Preference for robot service or human service in hotels? Impacts of the COVID-19 pandemic. (February 2021) - Kim, Seongseop (Sam); Kim, Jungkeun; Badu-Baiden, Frank; Giroux, Marilyn; Choi, Youngjoon
Highlights: This study examines choices that involve multiple options with human and robot facets. This study identifies preference for robot-staffed hotels over human-staffed hotels. This study shows preference for robot-staffed (vs. human-staffed) hotels when COVID-19 is salient. This study evidences the moderating role of perceived threat in consumers' choices in times of severe crisis. Abstract: Robots and artificial intelligence (AI) technologies are becoming more prominent in the tourism industry. Nowadays, consumers are faced with multiple options involving both human and robot interactions. A series of experimental studies were implemented. Four experiments demonstrated that consumers had a more positive attitude toward robot-staffed (vs. human-staffed) hotels when COVID-19 was salient. The results were different from previous studies, which were conducted before the COVID-19 pandemic. Since the moderating role of perceived threat in consumers' preference for robot-staffed hotels was significant, the respondents' preference was attributed to the global health crisis. This research provides a number of theoretical and managerial implications by improving the understanding of technology acceptance during a health crisis.